Economics / Second Edition - Sloman John (Prentice Hall, 1994)
Its broad coverage of the principles of economics includes a wealth of interesting examples and illustrations presented with first year undergraduates very clearly in mind. Preface, Introducing Economics, Supply and Demand, Government Intervention in the Market, Background to Demand, Background to Supply, Profit Maximizing Under Imperfect Competition, Alternative Theories of the Firm, The Theory of Distribution of Income, Markets and Efficiency and the Public Interest, Applied Microeconomics, Macroeconomic Ideas, Fiscal Policy, Money and Interest Rates, Monetary Policy, Supply-Side Policies, International Trade, Economic Development in the Third World, Index.